Protein-bound Uremic Toxins, Inflammation and Oxidative Stress: A Cross-sectional Study in Stage 3–4 Chronic Kidney Disease - Rossi, Megan; Campbell, Katrina L.; Johnson, David W.; Stanton, Tony; Vesey, David A.; Coombes, Jeff S.; Weston, Kassia S.; Hawley, Carmel M.; McWhinney, Brett C.; Ungerer, Jacobus P.J.; Isbel, Nicole (Archives of medical research, 2014)
Indoxyl sulfate (IS) and p-cresyl sulfate (PCS) are nephro- and cardiovascular toxins, produced solely by the gut microbiota, which have pro-inflammatory and pro-oxidative properties in vitro. We undertook this study to investigate the associations between IS and PCS and both inflammation and oxidative stress in the chronic kidney disease (CKD) population. In this cross-sectional observational cohort study, participants with stage 3–4 CKD who enrolled in a randomized controlled trial of cardiovascular risk modification underwent baseline measurements of serum total and free IS and PCS (measured by ultraperformance liquid chromotography), inflammatory markers (interferon gamma [IFN-γ], interleukin-6 [IL-6] and tumor necrosis factor-alpha [TNF-α]), antioxidant and oxidative stress markers (plasma glutathione peroxidase [GPx] activity, total antioxidant capacity [TAC] and F2-isoprostanes) and pulse wave velocity (PWV), a marker of arterial stiffness. There were 149 CKD patients (59% male; age 60 ± 10 years; 44% diabetic) with a mean eGFR of 40 ± 9 mL/min/1.73 m2 (range 25–59). Serum free and total IS were independently associated with serum IL-6, TNF-α and IFN-γ, whereas serum free and total PCS were independently associated with serum IL-6 and PWV. Free IS and PCS were additionally independently associated with serum GPx but not with TAC or F2-isoprostanes. IS and PCS were associated with elevated levels of selected inflammatory markers and an antioxidant in CKD patients. PCS was also associated with increased arterial stiffness. Inflammation and oxidative stress may contribute to the nephro- and cardiovascular toxicities of IS and PCS. Intervention studies targeting production of IS and PCS by dietary manipulation and the subsequent effect on cardiovascular-related outcomes are warranted in the CKD population.